Contextualizing the Meaning of the Siwak Hadith Through Fazlur Rahman's Hermeneutic Approach (A Substantive-Philosophical Understanding) - Fauzi, Ahmad (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2018)
This paper examines the Siwak Hadith. As is known there are many traditions that explain the virtues of siwak. Siwak is a thing that is very favored by the prophet Muhammad. At that time siwak became the main tool for oral cleansers. And the tools used are roots or branches of arak plants. Classical scholars have the same understanding of the tools for whistle, that is as practiced at the time of the Prophet Muhammad saw. Over time, oral cleaning devices were found and produced in various forms. Even siwak wood can be extracted and become a base for toothpaste. Related to this, the question that can be asked is can the siwak wood be replaced with other tools that have the same function as the purpose of the siwak service. Whether using these tools is considered to have carried out the Prophet's Sunnah. This study tries to contextualize the understanding of the Siwak Hadith according to the current situation. The approach used is Fazlur Rahman's hermeneutic approach. Through situational interpretation and using historical analysis it is hoped that the principles of religious teachings that Salih li Kulli Zaman wa Makan (relevant at all times and places) can be realized. Through this study, the authors conclude that modern oral cleaning tools such as toothpaste, sprey mouthwash and the like can replace siwak and have the same laws in religion.